2017
DOI: 10.1093/jat/bkx082
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for Toxicological Investigation of Drug-Impaired Driving and Motor Vehicle Fatalities—2017 Update

Abstract: This report describes the outcomes of a process undertaken to review and update the National Safety Council's Alcohol, Drugs and Impairment Division's recommendations for the toxicological investigation of suspected alcohol and drug-impaired driving cases and motor vehicle fatalities. The updates to the recommendations are made based on a survey of practices in laboratories in the USA and Canada performing testing in these cases, consideration of existing epidemiological crash and arrest data, current drug use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 6 publications
0
35
0
Order By: Relevance
“…Several studies have shown a correlation between seizure and long‐term tramadol use or abuse [121,123]; however, the reported seizure rate among tramadol poisoning varied in different studies [120,123,124]. There are also concerns regarding driving under the influence of tramadol from other countries [125,126]. Moreover, fatal cases due to tramadol consumption have been reported in the United States and European countries [127–131].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown a correlation between seizure and long‐term tramadol use or abuse [121,123]; however, the reported seizure rate among tramadol poisoning varied in different studies [120,123,124]. There are also concerns regarding driving under the influence of tramadol from other countries [125,126]. Moreover, fatal cases due to tramadol consumption have been reported in the United States and European countries [127–131].…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that in these circumstances, it is debatable and not cost effective to include these benzodiazepines in the panel of substances to be confirmed and quantified in the laboratory; there would be room for the assessment of other substances or resources to carry out more roadside drug tests, for example. In addition, benzodiazepines are medicines/drugs well known to impair driving, and recommendations for their assessment in drivers are provided [1,[28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Roadside drug tests detect cannabis, cocaine, amphetamine, methamphetamine and opioids but not benzodiazepines. While recommendations and guidelines for toxicological investigations of drug-impaired driving have been published [1,[28][29][30] and Spain follows DRUID recommendations [1], one issue that arises is whether it is rational to include benzodiazepines in the confirmation analysis at the laboratory if the devices used in the roadside drug test do not include the kit to detect benzodiazepines.…”
Section: Introductionmentioning
confidence: 99%
“…The available evidence verifies that saliva is a viable matrix for analysis of GHB but does not seem to offer any advantage over blood in terms of extending the window of detection [81,82]. However, obtaining samples of saliva is less invasive than drawing blood, which makes this fluid more convenient for off-site testing, such as drug screening in various populations, such as motorists [83,84]. Despite more water in saliva (99%) compared with whole blood (80%) the endogenous GHB concentrations were mostly lower in saliva [46].…”
Section: Salivamentioning
confidence: 99%